REVITALISASI RAGAM HIAS TRADISIONAL GAYA MATARAM DALAM PENGEMBANGAN DESAIN FURNITUR - Bagus Indrayana; Guntur - (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2009)
Among Indonesian original artworks, there are many of them which are claimed by foreign entrepreneurs or countries. Batik (Malaysia), decorative motifs of metalic handicraft (Cina), and carving furniture design from Jepara (England) were the examples. Keris and Wayang Kulit Purwa are officially validated by UNESCO as great creation from Indonesia. This fact leaded the anticipation to identify Indonesian traditional decorative patterns to avoid foreign claim. Cultural products from various suburban areas in Indonesia such as traditional decorative patterns in Mataram style in various kinds of technique and material that was an aesthetic element of daily need products in its era. Understanding the insights of motif, structure, function, application method, and also style and the symbolic meaning within, the techniques and the materials used in the creating process are essential to be explored using aesthetic approach. To make the traditional decorative pattern of Mataram style appropriate in the present and the future era, it needed to be revitalized by applying it as aesthetic element of creative and innovative furniture design within creative process of Indonesian craftsmen, so that it would possible competing among global culture era. Besides, such study needed to be supported by reference from relevant source, empirical observation and interview with relevant experts, such as culture observer, chief of deperindagkop (Official department of industry, trading and co-operation), entrepreneurs, craftsmen, and also practitioner of Usaha Kecil Menengah (UKM)-Lower-Middle Class Industry. As the result, beside to be treated as the basic idea in obtaining HAKI, this research would identify traditional Mataram style decorative pattern to provide innovative and creative furniture designs those reflecting Indonesian local wisdom. Besides reserving the intellectual rights for Indonesian craftsmen, collecting this decorative patterns were also claim-protected from other country. It would also increase and rearrange the values of national culture in the present and the future.Keywords: revitalized, traditional decorative patterns, furniture designs